Manajemen Berbasis Sekolah (MBS): Konsep Dasar dan Implementasinya pada Satuan Pendidikan - Alif Achadah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2019)
School based Management (SBM) is a model of management that grants autonomy to schools to organize their schooling independently. Independence is actually a responsibility given to the school, especially to the school principal in order to bring the progress of the school he leads. In its application, school based management requires extensive understanding of basic concepts. The article aims to discuss some basic concepts in implementing school based management by recommending one example of an institution that successfully implements it. Through literature study, the results of the study gave explanations on the basic concepts of management and school-based management and implementation problems as one of the decentralized policies of education organizing. An example of applying to an education unit shows that the school implementing the model is able to make the school a place for human resources empowerment and able to create a learning atmosphere that is enjoyable for students.